(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
The Covid-19 outburst both supply and demand shocks. Aggressive monetary stimulus that inject liquidity and support investment can offset the effect of demand and supply shock. Policy makers in the developing economies must access the efficiency and socioeconomic consequences of the moderation policies. In the short run the economic policy of the developing economy was dedicated on providing crisis relief to vulnerable population as in the short run it is not possible to stimulate the system. The study’s goal is to examine the impact of monetary stimulus package for the Indian economy to kick-start the economy out of the stagnation trap. This paper is an exploratory research. The data used in this paper is from the reports made by an international and national organisation like WHO, IMF, Report by Reserve bank of India, articles from newspapers, interviews by the experts in the field.